Radial Arterial Access for Hepatobiliary and Gastrointestinal Arterial Interventions: Initial Experience - Rachapalli, Vamsidhar; Jaganathan, Sriram; Palaniswamy, Mohnish; Tiruchunapalli, Deepashree; Chappidi, Sridhar; Inuganti, Srikar; Uthappa, Mangerira C. (Journal of Clinical Interventional Radiology ISVIR, 2018)
Introduction Radial artery access is being more commonly used for visceral and peripheral arterial interventions. Its use in the Indian subcontinent is not well reported. The aim of this study was to report outcomes of radial arterial access during arterial interventions of the hepatobiliary and gastrointestinal system.Methods In this retrospective study, patients who underwent radial artery access for hepatobiliary and gastrointestinal interventions from January 2015 to June 2017 were identified from the interventional database. Complications related to radial artery access and catheter placement in the visceral arteries, procedural modifications, and conversion to the standard femoral arterial access were analyzed.Results Total 32 patients were included in this study. Total 46 procedures (radial artery access) were performed. Nine patients had radial artery access on more than two occasions; 95% of the procedures involved interventional oncologic treatments. Patients were followed up for an average of 4 months following radial arterial access. Technical success was 98.7%. One patient developed radial artery spasm, and the access was abandoned. This patient subsequently underwent brachial arterial access. No patient required conversion to a femoral arterial access. No other complications were encountered during the follow-up. Compared with femoral arterial access, radial arterial access required longer catheters were needed for super selective catheterization of the visceral arteries.Conclusion Radial arterial access for arterial interventions in the hepatobiliary and gastrointestinal systems was technically feasible with no significant complications. Long catheters are required for selective catheterization of the visceral arteries with this approach.
Keywords: radial artery; access; technique